Preparation method of multilayer framework high-entropy ceramic nano aerogel

Through the preparation method of multi-layer architecture high-entropy ceramic based nanoaerogel, the multi-layer composite structure of hydrothermal synthesis and fiber-reinforced mesh fabric is used to solve the collapse problem of high-entropy ceramic aerogel in a high-temperature environment and the mechanical dimension problem in the preparation process, and achieve nanoaerogel materials with high mechanical strength, low thermal conductivity and high specific surface area.

CN119633701APending Publication Date: 2025-03-18AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411829914.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing high-entropy ceramic aerogel collapses in a high-temperature environment, making it difficult to meet the thermal insulation requirements of high-temperature areas. The prepared aerogels are in powder form, which are difficult to mechanically dimensional. The pore structure is micron-scale large pores, and the thermal insulation performance is poor.

Method used

The preparation method of multi-layer architecture high-entropy ceramic based nanoaerogel is adopted to prepare nanowires, nanorods or nanosheets high-entropy ceramic aerogels by hydrothermal synthesis. Combined with the multi-layer composite structure of fiber-reinforced grid fabric, the coordinated mechanism of directional adsorption, austenitic maturation and splitting model theory is carried out to form a uniform high-entropy ceramic phase.

Benefits of technology

The nanoframework of high-entropy ceramic aerogel is achieved with a thick nanostructure, low surface energy, high mechanical strength, small pore size, large specific surface area, high temperature resistance, low thermal conductivity, simple process and low cost, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633701A_ABST
    Figure CN119633701A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of multi-layer framework high-entropy ceramic nano aerogel, and belongs to the technical field of aerogel materials. The method comprises the following steps: adding metal oxide nanoparticles and inorganic acid into deionized water, and uniformly stirring and mixing at room temperature to obtain an acidic dispersion liquid; the method comprises the following steps: carrying out high-temperature and high-pressure hydrothermal reaction on an acidic dispersion liquid to prepare nanocrystal wet gel, pressing the nanocrystal wet gel into a wet gel thin layer with a certain thickness, flatly laying a fiber-reinforced grid fabric on the wet gel thin layer, repeating the step for several times to obtain multi-layer composite wet gel, and carrying out pressure maintaining on the multi-layer composite wet gel to obtain water-based multi-layer framework wet gel; and placing the water-based multi-layer framework wet gel in a low-surface-tension mixed solvent for solvent exchange to obtain low-surface-energy solvent-based multi-layer framework wet gel, and performing drying, high-temperature heat treatment and quenching on the low-surface-energy solvent-based multi-layer framework wet gel. The nano-skeleton of the high-entropy ceramic nanocrystal aerogel is thick and strong, and the problems of collapse, volume shrinkage and heat insulation failure of the nano-skeleton of the aerogel can be effectively avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a multilayer high-entropy ceramic nano aerogel, and belongs to the technical field of aerogel materials. Background Art

[0002] High-entropy ceramic aerogel is a new type of equimolar multi-component (generally greater than 5) ceramic porous material with excellent properties such as high temperature resistance, oxidation resistance, high hardness, wear resistance, and high stability. It has great application prospects in the fields of aerospace, aerospace technology, electronic manufacturing, and new energy. At present, the preparation method of high-entropy ceramic aerogel is mainly the sol-gel method. The three-dimensional nanoporous microstructure of the high-entropy ceramic aerogel prepared by the above method will collapse in a high temperature environment and cannot meet the growing demand for thermal insulation in high temperature areas. Most of the high-entropy ceramic aerogels reported so far are ceramic powder materials. For example, patent CN202210447639.9 discloses a low thermal conductivity high-entropy ceramic aerogel powder and a preparation method thereof. Inorganic lanthanum salts, inorganic strontium salts, inorganic barium salts and inorganic praseodymium salts are used as basic raw materials. High-entropy ceramic aerogel powder is prepared after sol-gel, normal pressure drying and high-temperature heat treatment; however, the high-entropy ceramic aerogel prepared by the above method exists in the form of powder, which is difficult to mechanically shape and cannot be used alone as a complete block.

[0003] Secondly, current technology makes it difficult to synthesize high-entropy ceramic aerogels with nanopore structure, high porosity, large specific surface area and complete block shape. For example, patent CN202210096551.7 discloses a nano high-entropy oxide aerogel and a preparation method thereof. The nitrate-sugar-alcohol solution is first freeze-dried, and then heat treated at 400-600°C to obtain a high-entropy oxide aerogel; however, the aerogel pore structure prepared by the above method is micron-scale macropores with extremely low specific surface area. The thermal radiation and thermal convection in a high-temperature thermal environment are extremely large, which seriously affects the thermal insulation performance of the material.

[0004] In addition, the basic components of high entropy ceramic aerogels are mostly nanoparticles, which are connected in series to form a "pearl necklace" structure. Such tiny neck connection points are difficult to form a continuous structure, which leads to the brittleness and instability of the aerogels, and it is very easy to lose powder. For example, patent CN202210757122.X discloses a (LaCeSmEuNd) 2 Zr 2 O 7The preparation method of high entropy oxide ceramic aerogel adopts the sol-gel method, introduces a colloid core dispersant and a coagulant, and uses a supercritical drying method to prepare a complete block of high entropy ceramic aerogel with a nanoporous structure, which is then ground and pressed into a sheet to obtain an aerogel product. The high entropy ceramic aerogel prepared by the above method is obtained by grinding, pressing and annealing, and has poor mechanical strength and is easy to fall off. It will cause nanotoxicity to the human body when diffused into the air.

[0005] Therefore, there is an urgent need to develop a preparation method for high-entropy ceramic nanoaerogels with high mechanical strength, small pore size, large specific surface area, good high temperature resistance, low thermal conductivity, simple operation and low cost. Summary of the invention

[0006] In order to solve the above problems, the technical solution adopted by the present invention is: to provide a method for preparing a multilayer high entropy ceramic-based nano-aerogel, the method comprising the following steps:

[0007] S1: adding metal oxide nanoparticles and inorganic acid into deionized water in a certain proportion, stirring and mixing at room temperature to obtain an acidic dispersion;

[0008] S2: subjecting the acidic dispersion to a high temperature and high pressure hydrothermal reaction to prepare a nanocrystal wet gel;

[0009] S3: Take an appropriate amount of nanocrystal wet gel, press it into a wet gel thin layer of a certain thickness, and lay the fiber-reinforced mesh fabric flat on the wet gel thin layer;

[0010] S4: repeating step S3 several times, and then spreading an appropriate amount of nanocrystal wet gel on the top to obtain a multilayer composite wet gel, and pressurizing the multilayer composite wet gel to obtain an aqueous multilayer structure wet gel;

[0011] S5: placing the aqueous multilayered wet gel in a low surface tension mixed solvent for solvent exchange to obtain a low surface energy solvent-based multilayered wet gel;

[0012] S6: drying the low surface energy solvent-based multilayer wet gel, and then subjecting it to high temperature heat treatment, and obtaining a multilayer high entropy ceramic nano-aerogel after quenching.

[0013] Preferably, the metal oxide described in step S1 is Y 2 O 3 , Gd 2 O 3 , Er 2 O 3 , Yb 2 O 3 、Lu 2 O 3 ,La 2O 3 、CeO 2 、Sm 2 O 3 、Eu 2 O 3 、Nd 2 O 3 、TiO 2 , HfO 2 、ZrO 2 、 2 O 5 , MgO, CoO, NiO, CuO, ZnO, B 2 O 3 、SiO 2 SnO 2 The invention relates to a method of preparing an aqueous solution of at least one of the above-mentioned metal oxide nanoparticles and a mixture of five or more thereof; the average particle size of the metal oxide nanoparticles is 5-50 nm; the inorganic acid is any one of nitric acid, hydrochloric acid, sulfuric acid, and phosphoric acid, or a mixture of several thereof; the certain proportion is a mass ratio of metal oxide nanoparticles: inorganic acid: deionized water of 1: (0.2-0.6): (20-50), wherein the selected metal oxide nanoparticles are in equimolar concentration.

[0014] Preferably, in step S2, the acidic dispersion is placed in a hydrothermal kettle for high-temperature and high-pressure hydrothermal reaction, the reaction temperature of the hydrothermal reaction is 200-280°C, the reaction time is 6-12h, and the reaction pressure is 3.0-4.2MPa; the microstructure of the nanocrystal wet gel is any one of nanowires, nanorods, and nanosheets.

[0015] Preferably, in step S3, an appropriate amount of nanocrystal wet gel is placed in a mold, and a four-column hydraulic press is used to press a wet gel thin layer of a certain thickness. The method of pressing a wet gel thin layer of a certain thickness by using a four-column hydraulic press is specifically performed as follows: using a four-column hydraulic press to quickly mold for 30-60 seconds at a pressure of 1.0-2.0 MPa, and then maintaining the pressure for 5-10 minutes at a pressure of 0.1-0.2 MPa to obtain a wet gel thin layer with a thickness of 0.5-5 mm, and placing it on the bottom layer; the material of the fiber-reinforced mesh fabric is any one of glass fiber, quartz fiber, aluminum silicate fiber, alumina fiber, and carbon fiber, and the fabric form is any one of plain weave, twill, and satin weave, with a thickness of 0.5-5 mm.

[0016] Preferably, in step S4, the multi-layer composite wet gel is pressurized using a hydraulic press; the step S3 is repeated several times for 5-10 times; the specific operation of pressurizing the multi-layer composite wet gel using a hydraulic press is: pressurizing the multi-layer composite wet gel at a pressure of 0.3-0.6MPa for 1-2h using a hydraulic press; the multi-layer structure wet gel comprises a thin layer of wet gel and a fiber reinforced mesh fabric layer, which are stacked in sequence from bottom to top, and the total number of layers is 13-23 layers.

[0017] Preferably, the low surface tension mixed solvent described in step S5 is ethanol mixed with one of n-hexane or aliphatic hydrocarbon naphtha or n-octane or naphtha or petroleum solvent oil or cyclohexane in a mixing mass ratio of 1: (0.5-2); the number of solvent exchanges is 2-4 times.

[0018] Preferably, the drying method described in step S6 is drying at room temperature and pressure for 6-12 hours; the conditions of the high-temperature heat treatment are: heating to 400-600°C at a heating rate of 0.5-2°C / min, then heating to 1000-1200°C at a heating rate of 1-3°C / min and keeping warm for 30-60 minutes, and finally heating to 1600-1800°C at a heating rate of 5-10°C / min and keeping warm for 0.5-2 hours; the quenching method is to use any one of high-pressure nitrogen, high-pressure air, high-purity helium, and high-purity argon to perform rapid air cooling quenching treatment on the aerogel; the pore size of the multilayer high-entropy ceramic nano aerogel is 2-50nm, and its crystal structure is one of rock salt structure, fluorite structure, perovskite structure, spinel structure, pyrochlore structure and olivine structure.

[0019] The present invention prepares a multilayer high entropy ceramic nano aerogel through the above steps, and its specific mechanism is as follows:

[0020] High-entropy ceramic nano-aerogels are prepared by hydrothermal synthesis, and a uniform and single high-entropy ceramic phase is formed based on the synergistic mechanism of nano-self-assembly, Ostwald ripening, and lattice distortion. First, the inorganic acid is ionized into hydrogen ions in the dispersion and uniformly adsorbed on the surface of metal oxide nanoparticles. Since the material has a strong solubility size dependence in the nanoscale range, the consumption of hydrogen ions by metal oxide nanoparticles during the growth process will eventually lead to the dissolution of smaller particles in the solution. Small-scale metal oxide grains will gradually gather together due to their larger curvature, higher energy, and higher solubility. Based on the thermodynamic crystal growth theory, the mutually aggregated metal oxide nanoparticles grow into a larger diameter metal oxide nanocrystal cluster, and then the nanocrystal cluster splits along the diameter direction during the hydrothermal reaction, obtaining multiple smaller metal oxide nanowires or nanorods or nanosheets as the basic structural units of the aerogel, which are formed into a three-dimensional network block with a nanoporous structure through disordered self-assembly, and finally high-entropy ceramic nano-aerogels are obtained after high-temperature calcination and quenching.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The present invention adopts a hydrothermal synthesis method, takes metal oxide nanoparticles as the main raw materials, and prepares high entropy ceramic aerogels with nanowire, nanorod or nanosheet crystal morphology based on the theories of directional adsorption, Ostwald ripening and splitting model. Compared with the nanoparticle-type high entropy ceramic aerogels prepared by the sol-gel method, the nano-skeleton of the high entropy ceramic nano-crystal aerogel is thick and has a low surface energy. After calcination at a temperature below the melting point of the material, sintering and fusion will not occur between the nano-crystals, which can effectively avoid the problems of aerogel nano-skeleton collapse, volume shrinkage and thermal insulation failure.

[0023] (2) The present invention adopts a multi-layered structural form for mechanical enhancement, using nano wet gel thin layers and fiber reinforced mesh fabrics to be stacked in sequence from bottom to top. During the compression molding process, the nano wet gel can penetrate the fabric mesh under the action of extrusion to form interconnections, effectively solving the problem of stratification of multi-layer composite aerogels after drying; in addition, the multi-layer fiber reinforced mesh fabric can greatly improve the shear strength of the composite aerogel material, thereby increasing the structural integrity and mechanical dimensionality of the aerogel material.

[0024] (3) The present invention adopts a normal pressure drying method to prepare a multilayer high entropy ceramic nano-aerogel, which does not require the cumbersome process of supercritical drying and freeze drying methods. The process is simple and easy to achieve large-scale industrial production. That is, the water-based multilayer wet gel is solvent-displaced by a low surface energy solvent, which eliminates the capillary tension difference between the inner and outer interfaces of the wet gel during the drying process at room temperature and pressure, effectively ensures the initial nanopore structure and size of the multilayer high entropy ceramic aerogel, and greatly reduces the preparation cycle and production cost of the high entropy ceramic aerogel material.

[0025] (4) The present invention adopts a staged high-temperature calcination and rapid air-cooling quenching process to obtain a multilayer high-entropy nano-ceramic aerogel, wherein the high-entropy effect can effectively inhibit the agglomeration and sintering of the basic structural units of the nanocrystalline aerogel during the high-temperature heat treatment process. The resulting large lattice distortion and smaller grain size can enhance the carrier transport barrier. Therefore, the porous structure of the aerogel and a large number of grain boundaries make the thermal insulation performance of the high-entropy nano-ceramic aerogel more excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0027] Figure 1 The multi-layer architecture (La 0.2 Ce 0.2 Sm 0.2 Eu 0.2 Nd 0.2 ) 2 Zr 2 O 7 TEM image of the basic structural unit of high entropy ceramic nanoaerogel;

[0028] Figure 2 The multi-layer architecture (Hf 0.2 Ce 0.2 Sm 0.2 Er 0.2 Y 0.2 ) 2 Zr 2 O 7 TEM image of the basic structural unit of high entropy ceramic nanoaerogel;

[0029] Figure 3 The multi-layer architecture (Mg 0.2 Co 0.2 Ni0.2 Cu 0.2 Zn 0.2 ) 2 Zr 2 O 7 SEM image of high entropy ceramic nanoaerogel;

[0030] Figure 4 The multi-layer architecture (Ti 0.2 Zr 0.2 Yb 0.2 Er 0.2 Ta 0.2 ) 2 Si 2 O 7 Schematic diagram of the multilayer structure of high-entropy ceramic nanoaerogel. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the preferred embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] A multi-layer architecture (La 0.2 Ce 0.2 Sm 0.2 Eu 0.2 Nd 0.2 ) 2 Zr 2 O 7 The preparation method of high entropy ceramic nano aerogel comprises the following steps:

[0034] S1: 100g of La with equal molar concentration 2 O 3 、CeO 2 、Sm 2 O 3 、Eu 2 O 3 、Nd 2 O 3 、ZrO 2 Nanoparticles (average particle size 10 nm) and 20 g of nitric acid were added to 2000 g of deionized water, and stirred and mixed at room temperature to obtain an acidic dispersion;

[0035] S2: placing the acidic dispersion prepared in S1 in a hydrothermal reactor, and preparing a nanowire wet gel through a high temperature and high pressure hydrothermal reaction, wherein the reaction temperature of the hydrothermal reaction is 200°C, the reaction time is 12h, and the reaction pressure is 3.0MPa;

[0036] S3: Take an appropriate amount of nanowire wet gel and place it in the mold. Use a four-column hydraulic press to quickly mold it at a pressure of 1.0 MPa for 60 seconds, and then maintain the pressure at a pressure of 0.1 MPa for 10 minutes to obtain a 0.5 mm thick wet gel layer, which is placed at the bottom layer. Then, a 0.5 mm thick glass fiber reinforced mesh plain fabric is laid flat on top of the wet gel layer.

[0037] S4: Repeat step S3 5 times, then spread an appropriate amount of nanowire wet gel on the top, and use a hydraulic press to maintain the pressure of the above-mentioned multi-layer composite wet gel for 2 hours at a pressure of 0.3MPa to obtain an aqueous multi-layer structure wet gel; the total number of layers of the multi-layer structure wet gel is 13 layers, including a wet gel thin layer and a glass fiber reinforced mesh plain fabric layer, which are stacked in sequence from bottom to top.

[0038] S5: placing the aqueous multilayer wet gel prepared in S4 in a mixed solvent of ethanol / n-hexane with a mass ratio of 1:1 and performing solvent exchange three times to obtain an ethanol / n-hexane solvent-based multilayer wet gel;

[0039] S6: The ethanol / n-hexane solvent system multilayer structure wet gel prepared in S5 was placed in a fume hood and dried at room temperature and pressure for 6 hours; the dried aerogel was subjected to high-temperature heat treatment in a tubular furnace: the temperature was raised to 400°C at a heating rate of 0.5°C / min, then raised to 1000°C at a heating rate of 1°C / min and kept warm for 30 minutes, and finally raised to 1600°C at a heating rate of 5°C / min and kept warm for 1 hour; the aerogel was then air-cooled and quenched with high-pressure nitrogen to obtain a multilayer structure (La 0.2 Ce 0.2 Sm 0.2 Eu 0.2 Nd 0.2 ) 2 Zr 2 O 7 High entropy ceramic nano aerogel has a pore size of 10nm and a fluorite structure.

[0040] Figure 1 The multi-layer architecture (La) prepared in the embodiment of the present invention 0.2 Ce 0.2 Sm 0.2 Eu 0.2 Nd 0.2 ) 2 Zr 2 O 7The TEM image of high-entropy ceramic nanoaerogel shows that the basic structural unit of the aerogel is a nanowire morphology.

[0041] Example 2

[0042] A multi-layer architecture (Hf 0.2 Ce 0.2 Sm 0.2 Er 0.2 Y 0.2 ) 2 Zr 2 O 7 The preparation method of high entropy ceramic nano aerogel comprises the following steps:

[0043] S1: 50g of HfO with equal molar concentration 2 、CeO 2 、Sm 2 O 3 , Er 2 O 3 , Y 2 O 3 、ZrO 2 Nanoparticles (average particle size 15 nm) and 30 g of hydrochloric acid were added to 2500 g of deionized water, and stirred and mixed at room temperature to obtain an acidic dispersion;

[0044] S2: placing the acidic dispersion prepared in S1 in a hydrothermal reactor, and preparing the nanorod wet gel through a high temperature and high pressure hydrothermal reaction, wherein the reaction temperature of the hydrothermal reaction is 220°C, the reaction time is 10h, and the reaction pressure is 3.2MPa;

[0045] S3: Take an appropriate amount of nanorod wet gel and place it in the mold. Use a four-column hydraulic press to quickly mold it at a pressure of 1.5 MPa for 50 seconds, and then maintain the pressure at a pressure of 0.15 MPa for 8 minutes to obtain a 0.8 mm thick wet gel layer, which is placed at the bottom layer. Then, a 0.8 mm thick quartz fiber reinforced mesh twill fabric is laid flat on top of the wet gel layer.

[0046] S4: Repeat step S3 10 times, then spread an appropriate amount of nanorod wet gel on the top, and use a hydraulic press to maintain the pressure of the above-mentioned multi-layer composite wet gel at 0.6MPa for 1 hour to obtain an aqueous multi-layer structure wet gel; the total number of layers of the multi-layer structure wet gel is 23 layers, including a wet gel thin layer and a quartz fiber reinforced mesh twill fabric layer, which are stacked in sequence from bottom to top.

[0047] S5: placing the water-based multilayer wet gel prepared in S4 in a mixed solvent of ethanol / aliphatic hydrocarbon naphtha in a mass ratio of 1:2 and performing solvent exchange 4 times to obtain an ethanol / aliphatic hydrocarbon naphtha solvent-based multilayer wet gel;

[0048] S6: The ethanol / aliphatic hydrocarbon naphtha solvent system multilayer structure wet gel prepared in S5 was placed in a fume hood and dried at room temperature and pressure for 8 hours; the dried aerogel was subjected to high-temperature heat treatment in a muffle furnace: the temperature was raised to 600°C at a heating rate of 2°C / min, then raised to 1200°C at a heating rate of 3°C / min and kept at this temperature for 60 minutes, and finally raised to 1800°C at a heating rate of 10°C / min and kept at this temperature for 2 hours; the aerogel was then subjected to air cooling and quenching treatment using high-pressure air to obtain a multilayer structure (Hf 0.2 Ce 0.2 Sm 0.2 Er 0.2 Y 0.2 ) 2 Zr 2 O 7 High entropy ceramic nano aerogel has a pore size of 50nm and a rock salt structure.

[0049] Figure 2 The multi-layer structure (Hf) prepared in the embodiment of the present invention 0.2 Ce 0.2 Sm 0.2 Er 0.2 Y 0.2 ) 2 Zr 2 O 7 The TEM image of high-entropy ceramic nanoaerogel shows that the basic structural unit of the aerogel is a nanorod morphology.

[0050] Example 3

[0051] A multi-layer architecture (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 ) 2 Zr 2 O 7 The preparation method of high entropy ceramic nano aerogel comprises the following steps:

[0052] S1: 150g of MgO, CoO, NiO, CuO, ZnO, ZrO 2 Nanoparticles (average particle size 30 nm) and 60 g of phosphoric acid were added to 5000 g of deionized water, and stirred and mixed at room temperature to obtain an acidic dispersion;

[0053] S2: placing the acidic dispersion prepared in S1 in a hydrothermal reactor, and preparing a nanosheet wet gel through a high temperature and high pressure hydrothermal reaction, wherein the reaction temperature of the hydrothermal reaction is 240°C, the reaction time is 8h, and the reaction pressure is 3.6MPa;

[0054] S3: Take an appropriate amount of nanosheet wet gel and place it in the mold. Use a four-column hydraulic press to quickly mold it at a pressure of 2.0 MPa for 40 seconds, and then maintain the pressure at a pressure of 0.2 MPa for 5 minutes to obtain a 3 mm thick wet gel layer, which is placed at the bottom layer. Then, a 3 mm thick alumina fiber reinforced mesh satin fabric is laid flat on top of the wet gel layer.

[0055] S4: Repeat step S3 8 times, then spread an appropriate amount of nanosheet wet gel on the top, and use a hydraulic press to maintain the pressure of the above-mentioned multi-layer composite wet gel at 0.4MPa for 1.5 hours to obtain an aqueous multi-layer structure wet gel; the total number of layers of the multi-layer structure wet gel is 19 layers, including a wet gel thin layer and an alumina fiber reinforced mesh satin fabric layer, which are stacked in sequence from bottom to top.

[0056] S5: placing the aqueous multilayer wet gel prepared in S4 in a mixed solvent of ethanol / n-octane with a mass ratio of 2:1 and performing solvent exchange twice to obtain an ethanol / n-octane solvent-based multilayer wet gel;

[0057] S6: The ethanol / n-octane solvent system multilayer structure wet gel prepared in S5 was placed in a fume hood and dried at room temperature and pressure for 7 hours; the dried aerogel was subjected to high-temperature heat treatment in a tubular furnace: the temperature was raised to 550°C at a heating rate of 1.5°C / min, then raised to 1050°C at a heating rate of 1.5°C / min and kept warm for 40 minutes, and finally raised to 1650°C at a heating rate of 6°C / min and kept warm for 0.5 hours; the aerogel was then air-cooled and quenched with high-pressure helium to obtain a multilayer structure (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 ) 2 Zr 2 O 7 The high entropy ceramic nano-aerogel has a pore size of 30nm and a spinel structure.

[0058] Figure 3 The multilayer structure (Mg) prepared in the embodiment of the present invention 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 ) 2 Zr 2 O 7 The SEM image of high-entropy ceramic nanoaerogel shows that the basic structural unit of the aerogel is a nanosheet morphology.

[0059] Example 4

[0060] A multi-layer architecture (Ti 0.2 Zr 0.2 Yb 0.2 Er 0.2 Ta 0.2 ) 2 Si 2 O 7 The preparation method of high entropy ceramic nano aerogel comprises the following steps:

[0061] S1: 200 g of equimolar concentration of TiO 2 、ZrO 2 , Yb 2 O 3 , Er 2 O 3 、 2 O 5 、SiO 2 Nanoparticles (average particle size 50 nm) and 100 g of a hydrochloric acid / sulfuric acid mixture of equal mass ratio were added to 8000 g of deionized water, and stirred and mixed at room temperature to obtain an acidic dispersion;

[0062] S2: placing the acidic dispersion prepared in S1 in a hydrothermal reactor, and preparing the nanorod wet gel through a high temperature and high pressure hydrothermal reaction, wherein the reaction temperature of the hydrothermal reaction is 260°C, the reaction time is 6 hours, and the reaction pressure is 3.9 MPa;

[0063] S3: Take an appropriate amount of nanorod wet gel and place it in the mold. Use a four-column hydraulic press to quickly mold it at a pressure of 1.8 MPa for 45 seconds, and then maintain the pressure at a pressure of 0.12 MPa for 6 minutes to obtain a 4 mm thick wet gel layer, which is placed at the bottom layer. Then, a 4 mm thick aluminum silicate fiber reinforced grid plain fabric is laid flat on top of the wet gel layer.

[0064] S4: Repeat step S3 6 times, then spread an appropriate amount of nanorod wet gel on the top, and use a hydraulic press to maintain the pressure of the above-mentioned multi-layer composite wet gel at 0.6MPa for 1.2 hours to obtain an aqueous multi-layer structure wet gel; the total number of layers of the multi-layer structure wet gel is 15 layers, including a wet gel thin layer and an aluminum silicate fiber reinforced grid plain fabric layer, which are stacked in sequence from bottom to top.

[0065] S5: placing the aqueous multilayered wet gel prepared in S4 in a mixed solvent of ethanol / cyclohexane with a mass ratio of 2:3 and performing solvent exchange 4 times to obtain an ethanol / cyclohexane solvent-based multilayered wet gel;

[0066] S6: The ethanol / cyclohexane solvent system multilayer structure wet gel prepared in S5 was placed in a fume hood and dried at room temperature and pressure for 9 hours; the dried aerogel was subjected to high-temperature heat treatment in a muffle furnace: the temperature was raised to 530°C at a heating rate of 0.8°C / min, then raised to 1030°C at a heating rate of 1.2°C / min and kept warm for 45 minutes, and finally raised to 1730°C at a heating rate of 7°C / min and kept warm for 0.8 hours; the aerogel was then air-cooled and quenched with high-pressure air to obtain a multilayer structure (Ti 0.2 Zr 0.2 Yb 0.2 Er 0.2 Ta 0.2 ) 2 Si 2 O 7 High entropy ceramic nano aerogel has a pore size of 50nm and a perovskite structure.

[0067] Figure 4 The multi-layer structure (Ti) prepared in the embodiment of the present invention 0.2 Zr 0.2 Yb 0.2 Er 0.2 Ta 0.2 ) 2 Si 2 O 7 Schematic diagram of the multilayer structure of high entropy ceramic nanoaerogel. It can be seen that the total number of layers of the aerogel is 15, which are stacked from bottom to top, including (Ti 0.2 Zr 0.2 Yb 0.2 Er 0.2 Ta 0.2 ) 2 Si 2 O 7 High entropy ceramic aerogel thin layer and aluminum silicate fiber reinforced grid plain fabric layer.

[0068] Example 5

[0069] A multi-layer architecture (Y 0.2 G 0.2 Er 0.2 Yb 0.2 Lu 0.2 ) 2 Zr 2 O 7 The preparation method of high entropy ceramic nano aerogel comprises the following steps:

[0070] S1: 300g of equimolar concentration of Y 2 O 3 , Gd 2 O 3 , Er2 O 3 , Yb 2 O 3 、Lu 2 O 3 、ZrO 2 Nanoparticles (average particle size 25 nm) and 70 g of sulfuric acid were added to 1000 g of deionized water, and stirred and mixed at room temperature to obtain an acidic dispersion;

[0071] S2: placing the acidic dispersion prepared in S1 in a hydrothermal reactor, and preparing a nanowire wet gel through a high temperature and high pressure hydrothermal reaction, wherein the reaction temperature of the hydrothermal reaction is 280°C, the reaction time is 6h, and the reaction pressure is 4.2MPa;

[0072] S3: Take an appropriate amount of nanowire wet gel and place it in the mold. Use a four-column hydraulic press to quickly mold it at a pressure of 1.8 MPa for 30 seconds, and then maintain the pressure at a pressure of 0.10 MPa for 9 minutes to obtain a 5 mm thick wet gel layer, which is placed at the bottom layer. Then, a 5 mm thick carbon fiber reinforced grid plain fabric is laid flat on top of the wet gel layer.

[0073] S4: Repeat step S3 9 times, then spread an appropriate amount of nanosheet wet gel on the top, and use a hydraulic press to maintain the pressure of the above-mentioned multi-layer composite wet gel at 0.4MPa for 1.8 hours to obtain an aqueous multi-layer structure wet gel; the total number of layers of the multi-layer structure wet gel is 21 layers, including a wet gel thin layer and a carbon fiber reinforced mesh plain fabric layer, which are stacked in sequence from bottom to top.

[0074] S5: placing the water-based multilayer wet gel prepared in S4 in a mixed solvent of ethanol / aliphatic hydrocarbon naphtha in a mass ratio of 3:2 and performing solvent exchange three times to obtain an ethanol / petroleum solvent oil-based multilayer wet gel;

[0075] S6: The ethanol / petroleum solvent oil solvent system multilayer structure wet gel prepared in S5 was placed in a fume hood and dried at room temperature and pressure for 11 hours; the dried aerogel was subjected to high temperature heat treatment in a tubular furnace: the temperature was raised to 580°C at a heating rate of 0.8°C / min, then raised to 1180°C at a heating rate of 2.5°C / min and kept warm for 45 minutes, and finally raised to 1800°C at a heating rate of 10°C / min and kept warm for 1.5 hours; the aerogel was then subjected to air cooling and quenching treatment using high-pressure argon gas to obtain a multilayer structure (Y 0.2 G 0.2 Er 0.2 Yb 0.2 Lu 0.2 ) 2 Zr 2 O 7The high entropy ceramic nano-aerogel has a pore size of 40nm and an olivine structure.

[0076] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a multilayer high entropy ceramic nanoaerogel, characterized in that: The following steps are involved: Adding metal oxide nanoparticles and inorganic acid into deionized water in a certain proportion, stirring and mixing at room temperature to obtain an acidic dispersion; The acidic dispersion is subjected to a high temperature and high pressure hydrothermal reaction to prepare a nanocrystal wet gel; Take an appropriate amount of nanocrystal wet gel, press it into a wet gel thin layer of a certain thickness, and lay the fiber-reinforced mesh fabric flat on the wet gel thin layer; Repeat the steps of preparing a thin layer of wet gel and laying the fiber-reinforced mesh fabric several times, and then lay an appropriate amount of nanocrystal wet gel on the top to obtain a multi-layer composite wet gel, and pressurize the multi-layer composite wet gel to obtain a water-based multi-layered wet gel; placing the aqueous multilayered wet gel in a low surface tension mixed solvent for solvent exchange to obtain a low surface energy solvent-based multilayered wet gel; The low surface energy solvent-based multilayer structure wet gel is dried and then subjected to high temperature heat treatment, and then quenched to obtain a multilayer structure high entropy ceramic nano aerogel.

2. The method according to claim 1, characterized in that The metal oxide is five or more of Y2O3, Gd2O3, Er2O3, Yb2O3, Lu2O3, La2O3, CeO2, Sm2O3, Eu2O3, Nd2O3, TiO2, HfO2, ZrO2, Ta2O5, MgO, CoO, NiO, CuO, ZnO, B2O3, SiO2, and SnO2; the average particle size of the metal oxide nanoparticles is 5-50nm; the inorganic acid is any one or a mixture of at least two of nitric acid, hydrochloric acid, sulfuric acid, and phosphoric acid; the certain ratio is a mass ratio of metal oxide nanoparticles: inorganic acid: deionized water of 1: (0.2-0.6):(20-50)。 3. The method according to claim 1, characterized in that The reaction temperature of the hydrothermal reaction is 200-280° C., the reaction time is 6-12 hours, and the reaction pressure is 3.0-4.2 MPa; the microstructure of the nanocrystal wet gel is any one of nanowires, nanorods, and nanosheets.

4. The method according to claim 1, characterized in that The method of taking a proper amount of nanocrystal wet gel and pressing it into a wet gel thin layer with a certain thickness comprises: taking a proper amount of the nanocrystal wet gel and placing it in a mold, using the four-column hydraulic press to quickly mold for 30-60 seconds at a pressure of 1.0-2.0 MPa, and then maintaining the pressure at a pressure of 0.1-0.2 MPa for 5-10 minutes to obtain a wet gel thin layer with a thickness of 0.5-5 mm.

5. The method according to claim 1, characterized in that: The material of the fiber-reinforced mesh fabric is any one of glass fiber, quartz fiber, aluminum silicate fiber, aluminum oxide fiber, and carbon fiber. The fabric form is any one of plain weave, twill weave, and satin weave, and the thickness is 0.5-5 mm.

6. The method according to claim 1, characterized in that The several times are 5-10 times; the pressurizing of the multi-layer composite wet gel is to use a hydraulic press to pressurize the multi-layer composite wet gel at a pressure of 0.3-0.6MPa for 1-2h; the multi-layer structure wet gel comprises a wet gel thin layer and a fiber reinforced mesh fabric layer, which are stacked in sequence from bottom to top, and the total number of layers is 13-23 layers.

7. The method according to claim 1, characterized in that The low surface tension mixed solvent is ethanol mixed with one of n-hexane or aliphatic hydrocarbon naphtha or n-octane or naphtha or petroleum solvent oil or cyclohexane in a mass ratio of 1: (0.5-2); the number of solvent exchanges is 2-4 times.

8. The method according to claim 1, characterized in that The drying is performed at room temperature and pressure for 6-12 hours; the high-temperature heat treatment conditions are: heating to 400-600°C at a heating rate of 0.5-2°C / min, then heating to 1000-1200°C at a heating rate of 1-3°C / min and keeping warm for 30-60 minutes, and finally heating to 1600-1800°C at a heating rate of 5-10°C / min and keeping warm for 0.5-2 hours; the quenching is to use any one of high-pressure nitrogen, high-pressure air, high-purity helium and high-purity argon to perform rapid air cooling quenching treatment on the aerogel.

9. The method according to claim 1, characterized in that: The pore size of the multilayer high entropy ceramic nano aerogel is 2-50nm, and its crystal structure is one of a rock salt structure, a fluorite structure, a perovskite structure, a spinel structure, a pyrochlore structure and an olivine structure.

10. A multilayer high entropy ceramic nanoaerogel prepared according to the method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • A nano-high-entropy oxide aerogel and its preparation method

    CN114405420B

  • A high-entropy ceramic aerogel powder with low thermal conductivity and its preparation method

    CN114656262B

  • Preparation method of (LaCeSmEuNd) 2Zr2O7 high-entropy oxide ceramic aerogel

    CN115141030A